Control of power, torque, and instability drive using in-shot variable neutral beam energy in tokamaks. (28th September 2016) - Pace, D.C.; Collins, C.S.; Crowley, B.; Grierson, B.A.; Heidbrink, W.W.; Pawley, C.; Rauch, J.; Scoville, J.T.; Van Zeeland, M.A.; Zhu, Y.B.
Abstract: A first-ever demonstration of controlling power and torque injection through time evolution of neutral beam energy has been achieved in recent experiments at the DIII-D tokamak (Luxon 2002 Nucl. Fusion 42 614). Pre-programmed waveforms for the neutral beam energy produce power and torque inputs that can be separately and continuously controlled. Previously, these inputs were tailored using on/off modulation of neutral beams resulting in large perturbations (e.g. power swings of over 1 MW). The new method includes, importantly for experiments, the ability to maintain a fixed injected power while varying the torque. In another case, different beam energy waveforms (in the same plasma conditions) produce significant changes in the observed spectrum of beam ion-driven instabilities. Measurements of beam ion loss show that one energy waveform results in the complete avoidance of coherent losses due to Alfvénic instabilities. This new method of neutral beam operation is intended for further application in a variety of DIII-D experiments including those concerned with high-performance steady state scenarios, fast particle effects, and transport in the low torque regime. Developing this capability would provide similar benefits and improved plasma control for other magnetic confinement fusion facilities.